The dead of winter : beware the Krampus and other wicked Christmas creatures - Clegg, Sarah (Algonquin Books of Chapel Hill, an imprint of Workman Publishing, a division of Hachette Book Group, Inc., 2024)
"Historian Sarah Clegg delves deep into the folklore of the Christmas season in Europe, detailing the way its terrifying and often debaucherous past continues to haunt and entertain us now in the twenty-first century"--